Analysis of Raw Material Inventory Control Using Economic Order Quantity (EOQ) Method at CV. XYZ - Wahyu Sidiq Saputra; Rieska Ernawati; Wiwik Anggraini Wulansari (International Journal of Computer and Information System (IJCIS), 2021)
Companies need a control over their products in maintaining the quality and quantity, to be able to always meet the demands and needs of consumers. CV. XYZ is a digital printing company which is located at Jl. Sunan Abinawa, Patebon District, Kendal Regency (in front of SMP 2 Patebon). Raw material inventory control in CV. XYZ still uses the manual calculation method. With the Economis Order Quantity (EOQ), the inventory of raw materials can be kept to a minimum, the cost is as low as possible, and the quality is better. Based on the results of research and data analysis shows that the application of the EOQ method in CV. XYZ can produce inventory cost efficiency. This means that the raw material procurement policy carried out by CV. XYZ so far has not been efficient and has not shown minimum costs. While the inventory costs that have been issued by the company are still greater when compared to companies implementing raw material inventory control using the EOQ method. The total cost of inventory issued based on company policy is Rp. 14,899,999, while by using the EOQ calculation method the total inventory of paper raw materials can be made smaller, namely as much as 45.4 with orders 4 times a year.